Sinonim Kata Bahasa Arab dari Terjemah Buku Alfu Lailah Walailah Lilathfal (Pendekatan Semantik Kontekstual) - Ani Susilawati; Ahmad Habibi Syahid (Mantiqu Tayr: Journal of Arabic Language, 2024)
The difficulty of finding synonyms between Arabic and Indonesian has become a problem for translators. This study aims to find an alternative process of translating Arabic synonyms found in the book alfu lailah walailah lil athfal by Najwa Husain Abdul Aziz. The book contains synonyms consisting of two words in one sentence. This form of synonym amounts to sixteen words spread across various pages. This research focuses on analyzing the synonyms and how they are translated both lexically and contextually. The object of this research is the book alfu lailah walailah lil athfal by Najwa Husain Abdul aziz. This study uses the contextual semantik approach that has been developed by K. Ammer's Contextual Theory which includes four kinds contexts: linguistic context, emotional context, situational context, and cultural context. This theory seeks to preserve the precise contextual meaning of the source language, so that both diction and content can be readily accepted and understood by the reader.  This literature research is conducted solely based on the facts and phenomena contained in the data. In collecting data, the author uses the observation method, where in linguistic research this type of method is called the listening method. Meanwhile, in analyzing the data, the author uses the intralungual pairing method, which refers to the meaning of elements in the language that are lingual in nature, such as matters concerning meaning, information, and context of speech. In applying this method the author uses two techniques; first, the comparative linking technique equalizes, second, the comparative linking technique differentiates. While in the process of presenting the results of data analysis, the author uses a formal method by presenting the data with two methods, namely describing the findings and presenting the findings through tables. Through several stages, the data can be obtained that in the process of translating synonymous words using contextual approach, there are three variations of translation methods according to the context of the sentence; first: synonymous words are translated into one sentence, second: translation of synonymous words into two words (both words that are side by side must be translated), third: synonymous words are translated into one word but by looking for alternative meanings that can cover the two words. In this way, the translation is understood by readers and matches the context of the sentence.